2017
DOI: 10.1002/app.45447
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nanostructured polyhedral oligomeric silsesquioxane on the physical properties of poly(vinyl alcohol)

Abstract: An effective amphiphilic polyhedral oligomeric silsesquioxane (POSS) encapsulated poly(vinyl alcohol) (PVA) nanocomposite was successfully fabricated by solution blending method. Anionic octa(tetramethylammonium) (Octa‐TMA) and poly(ethylene glycol) (PEG) were used as cage side groups in POSS (Octa‐TMA‐POSS and PEG‐POSS) for the present study. Transmission electron microscopic analysis revealed the uniform dispersion of POSS in the PVA matrix. Crystallinity of PVA/POSS system was computed from differential sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Figure illustrates the SEM micrographs of the tensile fractured surfaces of POSS incorporated PVA‐PEO blend membranes. The SEM image of the tensile fractured surface of pristine PVA shows branched crack propagation and nonlinear deformation of the surface . Here, PEG‐POSS embedded PVA‐PEO exhibits a fibrillar‐like structure, suggesting high strength and modulus.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Figure illustrates the SEM micrographs of the tensile fractured surfaces of POSS incorporated PVA‐PEO blend membranes. The SEM image of the tensile fractured surface of pristine PVA shows branched crack propagation and nonlinear deformation of the surface . Here, PEG‐POSS embedded PVA‐PEO exhibits a fibrillar‐like structure, suggesting high strength and modulus.…”
Section: Resultsmentioning
confidence: 94%
“…Both PEG‐POSS and Octa‐TMA‐POSS act as excellent mechanical reinforcing agents for the PVA‐PEO membrane and CMC enhances the miscibility of PVA‐PEO. In previous work, the mechanical properties of PEG‐POSS and Octa‐TMA‐POSS incorporated PVA were presented and it was observed that the mechanical stability of the PVA membrane increased in the presence of POSS molecules; this was further increased on blending with PEO . The blend membrane exhibits reduced elongation at break and improved stiffness due to good miscibility of the PVA and PEO polymers in the presence of CMC implying that the latter acts as a stabilizer of the PVA‐PEO blend.…”
Section: Resultsmentioning
confidence: 98%
“…As the k values decreases the adhesion between filler and polymer matrix increases. 49 Kunori and Geil 50 equation is given by,…”
Section: Mechanical Properties and Morphological Analysismentioning
confidence: 99%
“…Size dependent thermomechanical properties of the nanoparticulate composites. PVA is an eco-friendly, inexpensive, non-toxic, and biocompatible polymer and has extensively attracted research attention for development of coating, nanofiber, and bulk materials 18 . Particularly, the PVA nanocomposites have been appealing for a wide range of applications including biomedicine 19 , gas separation 20 , resistive switching 21 , opto-electronics 22 among others.…”
Section: Size Dependent Optical Properties Of the Nanoparticles Ftirmentioning
confidence: 99%
“…Particularly, the PVA nanocomposites have been appealing for a wide range of applications including biomedicine 19 , gas separation 20 , resistive switching 21 , opto-electronics 22 among others. Despite the remarkable potential of the PVA nanocomposites, it is mechanically weak and needs to be reinforced 18 . In this regard, controlled construction of the material by engineering of the www.nature.com/scientificreports www.nature.com/scientificreports/ nanofillers' characteristics e.g.…”
Section: Size Dependent Optical Properties Of the Nanoparticles Ftirmentioning
confidence: 99%